Code-division multiplexing of a sensor channel a software implementation. - Smith, J.R (IEEE Journal on selected areas in communications)
This paper demonstrates the use of software radio techniques in the context of sensing, rather than communications. It describes code-division multiplexing (CDMA) and time-division multiplexing (TDMA) of a receiver channel in an electric field sensing system. The only hardware used is a front-end gain stage consisting of two opamps and a microcontroller. The modulation and demodulation operations are implemented entirely in the microcontroller software. Multiple coded waveforms are transmitted simultaneously, and induce a combined signal on a single receive electrode. The combined signal, after passing through a single analog front end terminating in an analog-to-digital converter, is separated into the four original component signals by a software demodulation operation. The signal-to-noise ratio (SNR) achieved by the code-division multiplexed system given a fixed measurement time is compared to the SNR achieved by a time-division multiplexed implementation given the same total measurement time. The paper also compares the scaling of TDMA and CDMA performance with the number of transmitted channels and the number of demodulated channels